الحدود الجزائرية المغربية من معاهدة لالا مغنية 1845الى بروتوكول 1901 (مجلة الواحات للبحوث والدراسات, 2023)
ملخص:شكَّلت مسألة الحدود الجزائرية المغربية بداية من 1845م أحد أهَّم الدراسات التَّاريخية المُعاصرة، باعتبارها محّطةً بارزةً جسَّدت انتهاكات تُرابية دعمّتها الإدارة الاستعمارية وفق سياسة البروتوكولات التي تحفظ مصالحها وهذا ما ترتب عنه صِدامات جزائرية مغربية خلقت بدورها أزمة حدوديةً بين البلدين.  كلمات دالة : حدود، اتفاقية لالا مغنية، بروتوكول 1901، الجزائر، المغرب.Abstract:The issue of the Algerian-Moroccan border, beginning in 1845, was one of the most important contemporary historical studies, as it was a prominent station that embodied soil violations supported by the colonial administration in accordance with the policy of protocols that preserved its interests. This resulted in Algerian-Moroccan clashes that in turn created a border crisis between the two countries. Key words: Borders; Lalla Maghnia agreement; Protocol 1901; Algeria; Marocco.